Cohesion in Deaf Students’ Recount Texts: A Theme Analysis - Holik, Nici Azhari (Passage, 2019)
Being cohesive in writing for deaf students is very crucial as it is a mean of expressing idea to those who do not understand sign language. Thus, this study aims to analyze the cohesion of deaf students’ recount texts in terms of the choice of theme and thematic progression patterns. Using Halliday’s (1994) theory of functional grammar as its main theory, the present study investigates types of theme, thematic progression patterns, and how these two elements support the cohesion of deaf students’ recount texts. The data were collected from 36 recount texts from high achiever and low achiever students from three educational levels. In terms of theme choice, the findings show that low achiever students tend to employ more marked theme (63,64% of the total marked themes) as they lack of the ability to write a grammatically correct sentence. In terms of the thematic progression, theme reiteration pattern is the most frequent pattern employed by deaf students, indicating that they want to make a strong focus on the topic discussed in their recount texts. Keywords: cohesion; theme analysis; recount text; deaf students.